The Impact of Fiscal-Monetary Policy Interaction on the Indonesian Economy - Chairani Fadhila Pravitasari; Insukindro Insukindro (Jurnal Ekonomi Pembangunan, 2022)
This study seeks to examine the interactions between fiscal and monetary policies and their impact on output and inflation in Indonesia from 2003:4 to 2018:4 using Structural Vector Autoregression (SVAR). It is important to investigate the coordination between both because overall macroeconomic policy framework requires a close coordination between monetary and financial policies. The variables utilized are government spending, debt, output gap, tax, inflation, interest rate, and exchange rate obtained from the Indonesian Ministry of Finance, the Indonesian Statistics, and Bank of Indonesia. Government spending as a proxy for fiscal policy and interest rate as a proxy for monetary policy have a strategic complement relationship, whereas tax revenue as a proxy for fiscal policy and interest rate as a proxy for monetary policy have a strategic substitutes relationship.